2015
DOI: 10.5009/gnl14109
|View full text |Cite
|
Sign up to set email alerts
|

Functional Gastrointestinal Disorders in Young Military Men

Abstract: Background/AimsTo estimate the prevalence and evaluate the associated psychological factors of functional gastrointestinal disorders (FGIDs) in males in their twenties who are currently enrolled in military service.MethodsA total of 1,073 men in the Korean army were asked to complete questionnaires based on the Rome III criteria and Symptom Checklist-90-revised (SCL-90R). The prevalence of FGIDs was estimated, and the associated psychological factors were evaluated.ResultsA total of 967 men participated. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
4
7
0
Order By: Relevance
“…The anxiety factor was proved to be an independent risk factor for FGIDs, whereas no statistical correlation was observed between depression and FGIDs. This result was similar to a study of the brain–gut pathway 60 , but not coincident with some studies, which found that depression had a negative correlation with FGIDs 14 , 44 . The exact reason or mechanism was unclear.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The anxiety factor was proved to be an independent risk factor for FGIDs, whereas no statistical correlation was observed between depression and FGIDs. This result was similar to a study of the brain–gut pathway 60 , but not coincident with some studies, which found that depression had a negative correlation with FGIDs 14 , 44 . The exact reason or mechanism was unclear.…”
Section: Discussionsupporting
confidence: 91%
“…This study also found that FD was the most prevalent FGIDs overall (13.21%), followed by IBS (9.43%) and globus (7.08%). The main subtype rank was similar to that in other studies, such as Bang 44 , Wu 14 , and Dong 45 . However, the prevalence in this study was quite higher than these studies, which were reported as 5.85% and 4.04% for FD and IBS for the Chinese air forth pilots’ prevalence in Wu’s research 14 .…”
Section: Discussionsupporting
confidence: 87%
“…Among the study participants, 461 (37.9%) showed FGID with FH being the most common. This was lower than those reported by Park et al ., who indicated that the prevalence of FGID was 49.7% in patients visiting digestive clinics; however, this was much higher than the prevalence (18.5%) reported by Bang et al among young military men with high job stress. Moreover, the FH–FD and FH–IBS types were common among the overlapping FGID, which diverges from the results of a previous study in Korea, in which the IBS‐FD type was reported to be the most common …”
Section: Discussionmentioning
confidence: 72%
“…Of the participants, 81 patients (56.25%) showed FGID; this is higher than the prevalence of 49.7% reported by Park et al 27 in a study of patients at a digestive clinic, and much higher than the prevalence of 18.5% reported by Bang et al 28 in a study of military men experiencing high occupational stress. Also, unlike a previous study of the general population in South Korea, in which IBS-FD overlap was most common, 29 in our study, NERD-FD overlap was most common.…”
Section: Discussionmentioning
confidence: 55%